PERBEDAAN PENGETAHUAN IBU HAMIL TRIMESTER I SETELAH DIBERIKAN SELF MANAGEMENT EDUCATION MENGHADAPI EMESIS GRAVIDARUM DI BPM WILAYAH KERJA PUSKESMAS IV DENPASAR SELATAN: DIFFERENCES KNOWLEDGE OF PREGNANT WOMEN IN FIRST TRIMESTER AFTER BEING GIVEN SELF MANAGEMENT EDUCATION FACING EMESIS GRAVIDARUM AT PRIVATE PRACTICE MIDWIVES PUSKESMAS IV DENPASAR SELATAN - Witari, Ni Nyoman Deni; Dewianti, Ni Made (Stikes Wira Medika Bali, 2019)
Nausea, vomiting is one of the earliest, most common and most stressful symptoms in early pregnancy. Non-pharmacological therapy is a type of complementary therapy that can be used as an intervention to treat nausea. Emesis gravidarum's self management education adopts the concept of Corbin and Straus in Kate and Halsted, which is set forth in the form of a module that aims to enable pregnant women to educate themselves so as to be able to regulate their own lives, set goals, and provide self-reinforcement in dealing with nausea vomiting experienced. The purpose of this study was to determine differences in knowledge after self management education in dealing with emesis gravidarum. This research is an analytic study with a pre-experimental research design (quasi experiment design) with one group pre-test-post-test design. This research will be conducted at BPM Puskesmas IV Denpasar Selatan Work Area. The population of this study was pregnant women who came to BPM in the work area of ​​Puskesmas IV South Denpasar. The sample of this study was pregnant women who experienced nausea and vomiting in the first trimester who met the inclusion criteria where the sampling technique in this study was accidental sampling. Bivariate analysis will be conducted t test Test to test the differences between the two pre and post test distributions before given self management education and after giving self management education to face emesis gravidarum. the average knowledge before being given the self management module was 59.1, the standard deviation value was 10.856, the minimum and maximum values ​​were 33-87. The average value of knowledge after being given a self management module is 73.6, the standard deviation value is 13.874 with minimum and maximum values ​​of 47-100 Key Word : Knowledge, pregnant women In First Trimester ,Vomiting nausea